2011
DOI: 10.1111/j.1442-9071.2011.02651.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of nanoparticles using magnetic resonance imaging after intravitreal injection

Abstract: Background: Magnetic nanoparticles may be used for focal delivery for cells, plasmids or drugs, and other applications. Here we asked whether magnetic nanoparticles could be detected in vivo at different time points after intravitreal injection by magnetic resonance imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
5
15
0
Order By: Relevance
“…Moreover, the magnetic HCECs could be moved within a magnetic field (data under review). The absence of magnetic nanoparticle toxicity on HCECs in vitro matched our published data on a lack of toxicity when the nanoparticles were injected into rodent eyes in vivo [118,119]. By targeting injected HCECs to the endothelium with a uniform magnetic field, this cell therapy approach may decrease the potential risks of adverse effects such as trabecular meshwork clogging and increased intraocular pressure.…”
Section: Cell Replacement Therapies To Treat Corneal Endotheliumsupporting
confidence: 77%
“…Moreover, the magnetic HCECs could be moved within a magnetic field (data under review). The absence of magnetic nanoparticle toxicity on HCECs in vitro matched our published data on a lack of toxicity when the nanoparticles were injected into rodent eyes in vivo [118,119]. By targeting injected HCECs to the endothelium with a uniform magnetic field, this cell therapy approach may decrease the potential risks of adverse effects such as trabecular meshwork clogging and increased intraocular pressure.…”
Section: Cell Replacement Therapies To Treat Corneal Endotheliumsupporting
confidence: 77%
“…Other injection routes such as intra-peritoneal (IP) 255-257 , retroorbital, 51, 58 , intravitreal (inner cavity of the eyes for intraocular drug delivery), 258, 259 intra-muscular and subcutaneous injections have also been used as alternative methods for administration of the IONPs. Tsuchiya et al .…”
Section: Ionps Pharmacokineticsmentioning
confidence: 99%
“…Movement of particles from the vitreous into the surrounding ocular tissues also differed depending on size with larger microparticles shown to travel to the trabecular meshwork, whereas smaller nanoparticles moved to the trabecular meshwork and to the retina. In addition to this work, a recent study by Raju et al (2012) demonstrated differences in the elimination of iron oxide particles after intravitreal injection. 47 Larger (4 mm) iron oxide particles coated with polystyrene were shown by magnetic resonance imaging (MRI) to remain in the rat eye 5 weeks following administration, whereas smaller (50 nm) iron oxide particles coated with dextran were not found to reside in the eye after 5 weeks.…”
Section: Effect Of Nanoparticle Sizementioning
confidence: 82%
“…In addition to this work, a recent study by Raju et al (2012) demonstrated differences in the elimination of iron oxide particles after intravitreal injection. 47 Larger (4 mm) iron oxide particles coated with polystyrene were shown by magnetic resonance imaging (MRI) to remain in the rat eye 5 weeks following administration, whereas smaller (50 nm) iron oxide particles coated with dextran were not found to reside in the eye after 5 weeks. This data seems somewhat conflicting with the work by Sakurai and colleagues (2001), 46 where the residence time increased with decreased size.…”
Section: Effect Of Nanoparticle Sizementioning
confidence: 82%
See 1 more Smart Citation